Percutaneous endobiliary radiofrequency ablation and stents in management of hepatocellular carcinoma with bile duct tumor thrombus: Initial single‐institution experience. Issue 4 (5th May 2020) - Cui, Wei; Xu, Rongde; Wang, Yu; Shi, Feng; Li, Jiaping; Chen, Xiaoming
Abstract: Aim: Hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT) is a rare condition, but it can lead to hepatic failure and is associated with poor prognosis. Treatment for HCC with BDTT remains a challenge. This study aimed to retrospectively evaluate the safety and feasibility of percutaneous endobiliary radiofrequency ablation (EB‐RFA) and biliary metal stent placement as an alternative treatment for patients with HCC with BDTT. Methods: From October 2014 to December 2016, nine patients (all men, mean age 53.2 ± 12.0; range 40–70) who underwent percutaneous EB‐RFA and biliary metal stent placement for HCC with BDTT were included. Stent patency, overall survival, technical and clinical success rate and complications were investigated. Results: Median stent patency from the time of the first EB‐RFA was 6.0 months (95% CI, 5.4–6.6 months) and survival from the time of diagnosis was 6.0 months (95% CI, 2.2–9.8 months). Two of 9 patients underwent bilateral EB‐RFA and stent placement, one underwent unilateral EB‐RFA and stent‐in‐stent procedure, and one EB‐RFA as treatment for biliary metal stent occlusion. One patient who presented with stent occlusion underwent repeat ablations 182 days after the first ablation procedure and 53 days after the re‐ablation procedure. Combination therapy was administered to five patients. The technical and clinical success rate were 100% and 89% per patient. After treatment, serum direct bilirubin levels were notably decreased in eight patients. No major complications were observed. Minor complications included one bile duct bleeding, three postoperative abdominal pain and two cholangitis. Conclusion: Percutaneous EB‐RFA and biliary metal stent placement might be technically safe and feasible therapeutic options for patients with HCC with BDTT.